Cooperative Learning Model based on Tudang Sipulung with Ethnomathematics Approach - Rusli Rusli; Chusnul Chatimah Azis; Asdar Asdar; Abdul Rahman; Hastuty Hastuty (PT ARRUS Intelektual Indonesia, 2022)
Mindset the learner's dislike of mathematics creates interest and their motivation in learning to be low and impact on their learning outcomes. Therefore, teachers as facilitator required get choose method that true consequently learning get interaction Educational, Inspiring and fun. So, the purpose in this research is investigate Effectiveness of Cooperative Model based on Tudang Sipulung with an Ethnomathematics Approach because this method can be made solution from the problems. Sample in this research is class IX.1 which selected by cluster random sampling and from population entire student class IX Junior High School in Makassar City. Data Collected by Indicators Effectiveness Learning that is result learn that Analyzed in a descriptive and inferential whereas activity and response student both Analyzed in a Descriptive. Result analysis Descriptive show (1) average pretest and posttest student that is 25.29 and 86.55 (2) averages N-Gain student that is 0,82 with category tall (3) average activity student that is 3,40 with category active (4) average percentage response student that is 89,60% with category very positive. Result analysis inferential show (1) value average result learn student >76.9 (2) average N-Gain student >0.29. From this result concluded that Application of Cooperative Model Based on Tudang Sipulung with Ethnomathematics Approach effective Applied at Learning mathematics student class IX Junior High School in the City Makassar.